240 años de profesión docente en Colombia - Bayona-Rodríguez, Hernando; Urrego-Reyes, Luz Adriana (Educación y Ciudad, 2019)
The present research builds a narrative about the teaching profession in Colombia from its beginnings, when those who dedicate themselves to instruction were citizens who scarcely know how to read or write, until the present, moment in which the teaching consolidates as an academic and political force. For this, a documentary analysis was made, this includes texts and norms about teaching work and their living conditions. The narrative is organized chronologically in five periods that respond, both to events that mark the history of the country, as to happenings that affect the living conditions of teachers.